Practical considerations for territorial perfusion mapping in the cerebral circulation using super‐selective pseudo‐continuous arterial spin labeling - Schollenberger, Jonas; Figueroa, C. Alberto; Nielsen, Jon‐Fredrik; Hernandez‐Garcia, Luis (Magnetic resonance in medicine, 2020)
Purpose This paper discusses several challenges faced by super‐selective pseudo‐continuous arterial spin labeling, which is used to quantify territorial perfusion in the cerebral circulation. The effects of off‐resonance, pulsatility, vessel movement, and label rotation scheme are investigated, and methods to maximize labeling efficiency and overall image quality are evaluated. A strategy to calculate the territorial perfusion fractions of individual vessels is proposed. Methods The effects of off‐resonance, label rotation scheme, and vessel movement on labeling efficiency were simulated. Two off‐resonance compensation strategies (multiphase prescan, field map), cardiac triggering, and vessel movement were studied in vivo in a group of 10 subjects. Subsequently, a territorial perfusion fraction map was acquired in 2 subjects based on the mean vessel labeling efficiency. Results Multiphase calibration provided the highest labeling efficiency (P = .002) followed by the field map compensation (P = .037) compared with the uncompensated acquisition. Cardiac triggering resulted in a qualitative improvement of the image and an increase in signal contrast between the perfusion territory and the surrounding tissue (P = .010) but failed to show a significant change in temporal and spatial SNR. The constant clockwise label rotation scheme yielded the highest labeling efficiency. Significant vessel movement (>2 mm according to simulations) was observed in 50% of subjects. The measured territorial perfusion fractions showed good agreement with anatomical data. Conclusion Optimized labeling efficiency resulted in increased image quality and accuracy of territorial perfusion fraction maps. Labeling efficiency depends critically on off‐resonance calibration, cardiac triggering, optimal label rotation scheme, and vessel location tracking.